2018
DOI: 10.1530/ec-18-0030
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric and metabolic aspects of dopaminergic therapy: perspectives from an endocrinologist and a psychiatrist

Abstract: The dopaminergic treatment represents the primary treatment in prolactinomas, which are the most common pituitary adenomas and account for about 40% of all pituitary tumours with an annual incidence of six to ten cases per million population. The dopaminergic treatment includes ergot and non-ergot derivatives with high affinity for the dopamine receptors D1 or/and D2. Through the activation of the dopaminergic pathway on pituitary lactotrophs, the dopamine agonists inhibit the prolactin synthesis and secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…The FDA reporting increased progressively after 2006 and almost reached a plateau after 2009 (23). A recent review of DA-associated ICDs reported to the FDA indicated that 62% of the patients experiencing ICDs were treated for PD, 24% for RLS and 3.5% for hyperprolactinemia (24). The significantly higher number of reports in patients receiving DA therapy for PD and RLS support the involvement of mesolimbic D3 receptors; pramipexole and ropironole have higher D3 affinity than cabergoline and bromocriptine.…”
Section: Dopamine Agonist Therapy and Impulse Control Disordersmentioning
confidence: 99%
See 4 more Smart Citations
“…The FDA reporting increased progressively after 2006 and almost reached a plateau after 2009 (23). A recent review of DA-associated ICDs reported to the FDA indicated that 62% of the patients experiencing ICDs were treated for PD, 24% for RLS and 3.5% for hyperprolactinemia (24). The significantly higher number of reports in patients receiving DA therapy for PD and RLS support the involvement of mesolimbic D3 receptors; pramipexole and ropironole have higher D3 affinity than cabergoline and bromocriptine.…”
Section: Dopamine Agonist Therapy and Impulse Control Disordersmentioning
confidence: 99%
“…Of note, the patient did not have these problems 25 years previously when she took bromocriptine. Table 1 summarizes the individual case reports of ICD during DA therapy administered for prolactinomas (24,27,28,29,30,31).…”
Section: Dopamine Agonist Therapy and Impulse Control Disordersmentioning
confidence: 99%
See 3 more Smart Citations